Ragam Penggunaan Teknologi Informasi Dan Komunikasi (TIK) untuk Informasi Pertanian di Masa Pandemi - Siti Aisyah Rizki Nurrahmah; Asri Sulistiawati (Institut Pertanian Bogor, 2022)
Information and Communication Technology (ICT) has its power in providing major changes for the development of the world. ICT can be utilized by all fields of work, both tourism, education, health, and even agriculture. Therefore, at this time farmers must be able to follow the development of existing technology, it is intended that agricultural products can meet the food needs of the Indonesian people. In addition, with ICT tools, agricultural businesses can also be developed. This study aims to analyze the characteristics of the use of ICT for agriculture and analyze the level of use of ICT for farmers. The method used in this research is a survey method and is supported by qualitative data with in-depth interviews and literature study. The results showed several individual characteristics that were different from previous studies. The intensity of the use of ICT tools by farmers is included in the medium category with a variety of ICT uses that are currently often used, namely smartphones.